When the Kidney Looks Like Thyroid: Thyroidization of the Kidney as a Histological Pattern and Its Potential Clinical Correlation - A Scoping Review - Czaplinski, Mieszko; Król, Maria; Bruska, Natalia Marta; Bilyk, Andrii; Pustuła, Paweł; Patalong, Mikołaj; Błaszkowski, Bartłomiej; Kołodziej, Przemysław; Więckowska, Katarzyna; Wolski, Adam (Journal of Education, Health and Sport, 2026)
Background: kidney thyroidization is a histological pattern - atrophic renal tubules filled with eosinophilic, colloid-like casts resembling thyroid follicles. Regarded as a nonspecific marker of chronicity in renal disease, yet its biological significance, clinical correlations, and prognostic value remain poorly defined. Aim: to synthesize the existing literature on renal thyroidization. Material and methods: a scoping review of the available literature describing thyroidization of the kidney in human renal pathology was done. 2 databases were screened - PubMed & Scopus. Eligible sources included original studies, case series, case reports, and reviews addressing histological features, mechanisms & clinical contexts of thyroidization. Support information extracted from relevant textbooks recognized as authoritative on the renal pathology field. Results: the literature associates thyroidization with chronic tubulointerstitial damage, mostly in chronic kidney disease of diverse etiologies. The pattern reflects tubular atrophy with proteinaceous casts, interstitial fibrosis and chronic inflammation. Clinical correlations are rarely assessed; the presence of thyroidization is usually interpreted as a marker of long-standing injury. Reports suggesting links with disease duration, recurrent infection, or poor renal outcome remain largely descriptive. Conclusions: thyroidization of the kidney is a reproducible and distinctive histological pattern that functions primarily as a morphological signpost of chronicity. Its potential value as a semi-quantitative marker of disease duration, prior injury burden, or prognosis has not been studied. Future work integrating digital pathology, quantitative morphometry, and clinicopathological correlation may clarify whether thyroidization carries information beyond that conveyed by established chronicity indices.